Crosstalk Between Astrocytes and Microglia: An Overview - Matejuk, Agata; Ransohoff, Richard M. (Frontiers in Immunology, 2020)
Based on discoveries enabled by new technologies and analysis using novel computational tools, neuroscience can be re-conceived in terms of information exchange in dense networks of intercellular connections rather than in the context of individual populations, such as glia or neurons. Cross-talk between neurons and microglia or astrocytes has been addressed, however, the manner in which non-neuronal cells communicate and interact remains less well-understood. We review this intriguing crosstalk among CNS cells, focusing on astrocytes and microglia and how it contributes to brain development and neurodegenerative diseases. The goal of studying these intercellular communications is to promote our ability to combat incurable neurological disorders.